Penerapan Teknologi Tepat Guna (E-Ox Level) Kepada Kelompok Pembudidaya Ikan Lele di Desa Kepongpongan Kabupaten Cirebon - Billi Rifa Kusumah; Asep Kosta Jaya; Dein Iftitah; Ridwan Siskandar; Hana Lestari; Khaerul Umam; Dedi Supriadi (Unri Conference Series: Community Engagement, 2021)
Partners realize that the production of cultivated fish can still be increased, one of which is by monitoring water quality by providing aeration to maintain water health. Partners need a technological assistance that can improve the quality of results and production levels in a shorter time, and of course not incur large electricity costs from using this technology. This community service program activity is designed to solve partner problems. The proposal team provided a technology product called E-Ox Level, a proven technology to monitor pond water quality and control the aerator engine to keep it at optimum water quality standards. This technology is energy efficient, because it utilizes solar energy. This product can reduce operating costs and increase production yields. This program shows positive results. The results of its installation in the Budikdamber pond showed that the growth rate of fish length and weight was faster than the pond without the help of technology, and the mortality rate was recorded to be lower. These results are similar when the technological device is applied to larger biofloc ponds.